Cultural Theories of Postpartum Bleeding in Matlab, Bangladesh: Implications for Community Health Intervention - Sibley, Lynn M; Hruschka, Daniel; Kalim, Nahid; Khan, Jasmin; Paul, Moni; Edmonds, Joyce K; Koblinsky, Marjorie A (Journal of Health, Population and Nutrition, 2009)
Early recognition can reduce maternal disability and deaths due to postpartum haemorrhage. This study identified cultural theories of postpartum bleeding that may lead to inappropriate recognition and delayed care-seeking. Qualitative and quantitative data obtained through structured interviews with 149 participants living in Matlab, Bangladesh, including women aged 18-49 years, women aged 50+ years, traditional birth attendants (TBAs), and skilled birth attendants (SBAs), were subjected to cultural domain. General consensus existed among the TBAs and lay women regarding signs, causes, and treatments of postpartum bleeding (eigenvalue ratio 5.9, mean competence 0.59, and standard deviation 0.15). Excessive bleeding appeared to be distinguished by flow characteristics, not colour or quantity. Yet, the TBAs and lay women differed significantly from the SBAs in beliefs about normalcy of blood loss, causal role of the retained placenta and malevolent spirits, and care practices critical to survival. Cultural domain analysis captures variation in theories with specificity and representativeness necessary to inform community health intervention. Key words: Anthropometry, Cultural; Maternal mortality; Morbidity; Postpartum haemorrhage; Bangladesh doi: 10.3329/jhpn.v27i3.3380 J Health Popul Nutr 2009 Jun;27(3):379-390